Quality assessment of pollen of pear genotypes for their use in breeding - N. S. Kiseleva (Новые технологии, 2019)
The morphological quality indices of pollen of 14 pear genotypes have been studied in the conditions of the humid subtropics of the south of Russia. Viability and fertility have been determined, and variational curves of pollen grain sizes have been analyzed to identify indirectly trends in microsporogenesis disturbance. A variation in the percentage of germination has been noted in the range from 55% to 83%, and fertility in the range of 77-97 %. The regularities of dimensional differentiation of pollen grains and other pollen quality parameters have been revealed, and the law of their distribution has been evaluated.As a result of statistical analysis, it has been found that an increase in the diameter of pollen grains is displayed by a greater uniformity of the graphic curve with a deviation of the distribution in the direction of decreasing values. Morphologically homogeneous pollen with volumes of sample sizes close to zero kurtosis and asymmetry are considered to be the result of the absence of disturbances in gamete formation as a result of meiotic fission and pollen formation in anthers.With minor violations of meiosis, the amount of pollen of different sizes is minimal, while there is an increase in the dispersion of the trait and an extension of the range of extreme values. A significant deviation of the variational curve of pollen sizes indicates changes in the process of microsporogenesis that caused morphological heterogeneity of pollen grains.